Magnetism and transition metal complexes - Mabbs, F.E.; Mabbs, F.E.; Machin, D.J. (London, Wiley, 1973)
his detailed view of calculation methods involved in magnetic properties of transition metal complexes starts at an elementary level and proceeds gradually through theory and calculations to offer sufficient background for original work. Topics include free ions and crystal field theory, perturbation theory, and magnetism of polynuclear species. 1973 edition.
Index, 204-206p.; New copyright 2008
Keywords: Magnetic properties; Perturbation theory; Free ions and crystal field theory